The Effects Of Multiple Energy Storage On The Capacity And Performance Of Hydro-Pneumatic Driveline - Wasbari, Faizil; Salim, Mohd Azli; Sukri, Mohamad Firdaus; Gan, Leong Ming; Sukri, Mohamad Firdaus; Mohd Shah, Hairol Nizam; Herawan, Safarudin Gazali (Universiti Malaysia Perlis, 2020)
The study is related to the effect of multiple energy storage on the capacity and performance of hydro-pneumatic driveline. The plan is to make the driveline operates on the hydro-pneumatic hybrid passenger car. The greatest challenge in developing a hydro-pneumatic hybrid passenger car is how to provide enough and optimum provision storage systems. Energy capacity affects the performance of a hybrid driveline, and it can be increased by increasing the size of the energy storage. However, the passenger car space is minimal. Therefore, one of the solutions is to use smaller storage, but more in numbers. Its small size allows it to be placed in several suitable locations in the car while the number increases the storage capacity. An experiment was carried out to see the multiple storage system behaviours to operate at the low-pressure level. Through the experiment, it was found that the multiple storages produced better power and discharged time compared to single storage. However, the torque and efficiency had an adverse effect because of the increase in motor speed and flow disturbance. The lowest efficiency recorded by the experiment was 40%, and the highest was 55%. In conclusion, the multiple storage systems are possible to be adapted to the hybrid hydro-pneumatic passenger car. However, some tweaks on component efficiency and lightweight material need to be considered.